Polypeptide-Based Molecular Platform and Its Docetaxel/Sulfo-Cy5-Containing Conjugate for Targeted Delivery to Prostate Specific Membrane Antigen - Petrov, Stanislav A.; Machulkin, Aleksei E.; Uspenskaya, Anastasia A.; Zyk, Nikolay Y.; Nimenko, Ekaterina A.; Garanina, Anastasia S.; Petrov, Rostislav A.; Polshakov, Vladimir I.; Grishin, Yuri K.; Roznyatovsky, Vitaly A.; Zyk, Nikolay V.; Majouga, Alexander G.; et al. (Molecules (Basel, Switzerland), 2020)
A strategy for stereoselective synthesis of molecular platform for targeted delivery of bimodal therapeutic or theranostic agents to the prostate-specific membrane antigen (PSMA) receptor was developed. The proposed platform contains a urea-based, PSMA-targeting Glu-Urea-Lys (EuK) fragment as a vector moiety and tripeptide linker with terminal amide and azide groups for subsequent addition of two different therapeutic and diagnostic agents. The optimal method for this molecular platform synthesis includes (a) solid-phase assembly of the polypeptide linker, (b) coupling of this linker with the vector fragment, (c) attachment of 3-aminopropylazide, and (d) amide and carboxylic groups deprotection. A bimodal theranostic conjugate of the proposed platform with a cytostatic drug (docetaxel) and a fluorescent label (Sulfo-Cy5) was synthesized to demonstrate its possible sequential conjugation with different functional molecules.